Examining the Effect of Explicit Reading Instruction on the Engagement of Elementary Students with Challenging Behaviors. Issue 2 (15th March 2022) - Evanovich, Lauren L.; Scott, Terrance M.
ABSTRACT: Providing support to students with challenging behaviors is a critical focus of classroom teachers' success. Finding ways to prevent and mediate academic and behavioral difficulties is a high priority area for both research and practice. The focus of this study is on the effects of implementation of Orton–Gillingham Reading intervention strategies on active engagement for students with challenging behaviors. Using a single-subject alternating treatments design across 3 elementary school classrooms, increasing the rate of teachers' positive feedback and opportunities to respond was examined for effect on the engagement of students identified with challenging behaviors. Future research directions and implications for recommended teacher practice are provided.